A pooled analysis of pancreatic resection for metastatic renal cell carcinoma - Zhou, Yanming; Wang, Xiao; Chen, Shi; Wang, Shijie (Frontiers in Oncology, 2024)
BackgroundPancreatic metastasis from renal cell carcinoma (PMRCC) is unusual and there is no consensus on its treatment. The present study aims to evaluate the clinical outcomes of surgical resection for PMRCC.MethodsPubMed and Web of Science were searched for Eligible studies from January 1980 to January 2024. Individual-patient data were pooled.ResultsA total of 436 participants were identified. The morbidity and 90-day mortality were 38.1% and 3.4%, respectively. Post-pancreatectomy recurrence occurred in 44.1% of the patients. The overall median survival was 116 months, with a 3-, 5- and 10-year survival rate of 85.3%, 76.6%, and 46.5% respectively. On univariate analysis, repeat metastasectomy was associated with a significantly better prognosis (P =0.003).ConclusionThese data suggest that surgical resection is a safe and effective therapeutic option for PMRCC. Repeat metastasectomy is positively suggested for recurrent disease provided all metastases can be removed curatively. Systematic review registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD42024525218.